Hubungan Antara Jumlah Asupan Karbohidrat Sederhana dan Lemak Trans dengan Tingkat Keparahan Stenosis Arteri Koroner Berdasarkan Skor Gensini di RS Kariadi Semarang - Yudhanta Suryadilaga; Sodiqur Rifqi; Sefri Noventi Sofia; Niken Puruhita; Suhartono Suhartono (RSUP Dr. Kariadi, 2025)
BACKGROUND: Coronary artery disease accounts for 111 million (27%) out of 400 million cases of cardiovascular disease worldwide. Regular consumption of foods high in trans fats and simple carbohydrates is a major cause of increased blood lipid and glucose levels, which are key risk factors for coronary artery disease. AIMS: This researches to examine the relationship between the amount of simple carbohydrate and trans fat intake and the severity of coronary artery stenosis based on the Gensini score. METHODS: This research used a cross-sectional observational design involving 56 patients with chronic coronary syndrome who had undergone coronary angiography and were found to have stenosis in their coronary arteries. The parameters assessed included the amount of simple carbohydrate intake, trans fat intake, LDL levels, HDL levels, triglyceride levels, HbA1C levels, hs-CRP levels, oxLDL levels, and Gensini score. RESULTS: There was a significant relationship between the amount of simple carbohydrate intake and the severity of coronary artery stenosis based on the Gensini score (p=0.004), and between the amount of trans fat intake and the severity of coronary artery stenosis based on the Gensini score (p=0.02). Additionally, there was a significant relationship between trans fat levels and LDL levels (p=0.017), and oxLDL levels (p=0.014), but not with HDL, triglyceride, or hs-CRP levels (p>0.05). Confounding variables such as age, gender, socioeconomic status, body mass index, hypertension, diabetes mellitus, dyslipidemia, statin use, antidiabetic drug use, physical activity, and statin use showed no significant relationship (p>0.05). CONCLUSION: There is a significant relationship between the amount of simple carbohydrate and trans fat intake and the severity of coronary artery stenosis based on the Gensini score.